Evaluation of Complementary and Alternative Medicine Practices Use in Patients with Chronic Obstructive Pulmonary Disease: Assessment of Beliefs and Medication Adherence - Betulay Kilic; Fatma Ilknur Cinar; Gulfaden Akkoc and Yakup Arslan (Professor Despina Sapountzi-Krepia, 2024)
Evaluation of Complementary and Alternative Medicine Practices Use in Patients with Chronic Obstructive Pulmonary Disease: Assessment of Beliefs and Medication Adherence